Tradisionalisme dan Modernisme Studi tentang nilai-nilai dalam Kehidupan Masyarakat Islam Kota Jambi - Chatib, Adrianus (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
This article highlights the development of contemporary velues of Jambis society. Employing the framework of thinking based on toth traditionalism and modernism concepts, the writer uncovers the long-rooted but alive traditions especially fot the homogeneous natives and non-natives. In the contrary, modern values are also developed especially for the educated urban people and the migrants who typically are heeogeneous.